Identificación y cuantificación de las saponinas contenidas en el fruto de la especie cucumis dipsaceus por cromatografía de líquidos de alta resolución (HPLC) - Paredes Mariños, Hugo Fernando (2007)
The present work consisted of to identify the type of saponins using qualitative reactions and at the same time to quantify the saponins from Cucumis dipsaceus species, “soap land” by Chromatography of Liquids of High Resolution (HPLC). In this way, we decided to adopt a new approach in order to achieve the objectives. First, the saponins were extracted by maceration, the first time in hexan and the second time in water. Then it suffered consecutive extractions using increasing solvent polarity; chloroform, ethyl acetate and n-butanol, as a result we obtained a pulverulent and off-white product. The hydrolyzes was done with hydrochlorate acid. The mixture was refluxed in a Maria bath between 68-70ºC for 20 minutes. The sapogenins released were extracted with chloroform. It was prepared solutions of experimental patron saponins by means of which the calibration curve was obtained; that it was good to quantify for HPLC the saponins of the Cucumis dipsaceus. The analysis cromatographic was carried out with a cromatographo HPLC HP1050 equipped with a column Lichrospher 100 RP - 8, 5 μm, 125 x 4 mm HP, with detection to 264 nm, to 2 mL/min and mobile phase methanol grade HPLC. The chemical analysis allows to conclude that in the extracted product and purified of Cucumis dipsaceus saponins triterpenids pentacycle exists to the concentration of 67%. The sugars of the hydrolized are not glucose and fructose neither.